Key concepts in social research - Payne, Geoff (SAGE, 2004)
This clearly written and user-friendly book is ideal for students or researchers who wish to get a basic, but solid grasp of a topic and see how it fits with other topics. By following the links a student can easily and efficiently build up a clear conceptual map of social research' - Malcolm Williams, Reader in Sociology, Cardiff University `This is a really useful book, written in an accessible manner for students beginning their study of social research methods. It is helpful both as an introductory text and as a reference guide for more advanced students. Most of the key topics in methods and methodology are covered and it will be suitable as a recommended text on a wide variety of courses' - Clive Seale, Brunel University At last, an authoritative, crystal-clear introduction to research methods which really takes account of the needs of students for accessible, focused information to help with undergraduate essays and exams. The key concepts discussed here are based on a review of teaching syllabi and the authors' experience of many years of teaching. Topics range over qualitative and quantitative approaches and combine practical considerations with philosophical issues. They include several new topics, like internet and phone polling, internet searches, and visual methods. Each section is free-standing, can be tackled in order, but with links to other sections to enable students to cross-reference and build up a wider understanding of central research methods. To facilitate comprehension and aid study, each section begins with a definition. It is followed by a summary of key points with key words and guides to further reading and up-to-date examples. The book is a major addition to undergraduate reading lists. It is reliable, allows for easy transference to essays and exams and easy to use, and exceptionally clearly written for student consumption. The book answers the needs of all those who find research methods daunting, and for those who have dreamt of an ideal introduction to the subject.